2020
DOI: 10.3174/ajnr.a6422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aortic Arch Anatomy on Technical Performance and Clinical Outcomes in Patients with Acute Ischemic Stroke

Abstract: BACKGROUND AND PURPOSE: Arterial access is a technical consideration of mechanical thrombectomy that may affect procedural time, but few studies exist detailing the relationship of anatomy to procedural times and patient outcomes. We sought to investigate the respective impact of aortic arch and carotid artery anatomy on endovascular procedural times in patients with large-vessel occlusion. MATERIALS AND METHODS: We retrospectively reviewed imaging and medical records of 207 patients from 2 academic institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
0
18
2
Order By: Relevance
“…Our study confirms the associations between tortuosity of the cervical ICA and long procedural duration shown by others. 5,6 Moreover, other studies showed associations for aortic arch elongation and aortic variants, [5][6][7][8] which were not found in our population. This difference might be due to the relative low prevalence of severe aortic arch elongation (17%) compared with two other studies (30%-39%), 7,8 and the relatively low prevalence of aortic variant C (11%) in our study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our study confirms the associations between tortuosity of the cervical ICA and long procedural duration shown by others. 5,6 Moreover, other studies showed associations for aortic arch elongation and aortic variants, [5][6][7][8] which were not found in our population. This difference might be due to the relative low prevalence of severe aortic arch elongation (17%) compared with two other studies (30%-39%), 7,8 and the relatively low prevalence of aortic variant C (11%) in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…3 Current recommendations state that procedural time should not exceed 60 minutes and the target should be successful recanalization defined as restored antegrade flow of ≥50% of the territory of the previously occluded artery. 4 Recent studies demonstrated that unfavorable extracranial vascular anatomy, including complex configuration of the aortic arch and tortuosity of the supra-aortic vessels, prolongs procedural duration, [5][6][7] and negatively influences revascularization success. 5,7,8 However, these studies were performed with small sample sizes leaving uncertainty about the true association between vascular characteristics and procedural duration and revascularization success, especially in addition to baseline predictors.…”
Section: Introductionmentioning
confidence: 99%
“…On logistic regression analysis, a type III aortic arch was the only patient characteristic associated with Fubuki failure, which was unsurprising given previous studies associating complicated arch anatomy with the inability to perform MT. 5 Nevertheless, as depicted in our representative case, the Fubuki was able to cross relatively tortuous arch anatomy while providing adequate support to complete the MT. In the future, more indepth anatomic analyses of MT cases may allow improved quantification of guide catheter performance and facilitate comparison among different catheters.…”
Section: Discussionmentioning
confidence: 61%
“…The articles with most interactions included a systematic review on transradial access, 11 and original research institutional studies. 21,22 English (98.2%) and Japanese (0.6%) were the most common languages utilized for the tweets. Physicians authored only 35.6% of the tweets, while 50.5% of accounts were from individuals whose careers were not specifically denoted by their profiles or biography and were listed as unknown.…”
Section: #Radialforneuromentioning
confidence: 99%